The constitutionalization of administrative law as a remedy for authoritarian rule : The case of Poland and the case of Germany - Kusiak-Winter, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The The continuity of the administrative apparatus is an indispensable element of any state, be it a democracy or an authoritarian regime. Given that permanency is an attribute of administration, any change from authoritarianism to democracy must therefore be followed by finding adequate corrective measures to transform public administration accordingly. In post-war Germany, it was the constitutionalisation of administrative law that had the pivotal role in attainingth is goal. The paper aims at shedding more light on how to view and critique the Polish departure from the administration of the PRL-era authoritarian system in the context of the path followed by Germany.
Keywords: constitutionalisation; administrative law; administration of PRL; Germany